Factors related to smoking status among male junior high school students in Kulon Progo Regency in 2016 - Sinaga, Merlyn; Prabandari, Yayi Suryo; Ahmad, Riris Andono (Berita Kedokteran Masyarakat, 2021)
Purpose: This study aims to identify factors associated with smoking status in junior high school students in Kulon Progo. Methods: This study was an observational analytic study with a cross-sectional design. A total of 397 male junior high school students in grades 7, 8, and 9 were the subjects in this study. Sampling in this study used a cluster random sampling technique. Data were collected using a structured questionnaire in November-December 2016. Data were analyzed with a simple Poisson regression and multiple Poisson regression with robust variance estimators. Results: Prevalence of smokers (ever smoker in last 30 days) among male junior high school students was 33.5%. Factors associated with smoking behavior in junior high school student was had one or more friends who smoke with aPR=16.43 (95% CI = 2.34 to 115.30; p-value = 0.005), had a positive attitude towards smoking by aPR= 1.90 (95% CI = 1.29 to 2.80; p-value = 0.001), had a positive subjective norm family towards smoking behavior with an aPR=1.53 (95% CI = 1.15 to 2, 04; p-value = 0.004), and have a low self-efficacy with an aPR=3.10 (95% CI = 1.88 to 5.11; p-value = 0.000). Conclusions: The role of parents, schools and education office and health office are necessary to shape the attitude toward smoking that smoking is harmful (bad) for adolescent, subjective norm that smoking behavior is not approved by their environment, and increase self-efficacy for not smoking by reducing the temptation to smoke from the home and school environment.